2014
DOI: 10.1093/carcin/bgu177
|View full text |Cite
|
Sign up to set email alerts
|

DNA glycosylase activity and cell proliferation are key factors in modulating homologous recombination in vivo

Abstract: Cancer susceptibility varies between people, affected by genotoxic exposures, genetic makeup and physiological state. Yet, how these factors interact among each other to define cancer risk is largely unknown. Here, we uncover the interactive effects of genetical, environmental and physiological factors on genome rearrangements driven by homologous recombination (HR). Using FYDR mice to quantify HR-driven rearrangements in pancreas tissue, we show that DNA methylation damage (induced by methylnitrosourea) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 54 publications
(87 reference statements)
3
20
0
Order By: Relevance
“…Four independent studies were performed and analysis of the approximate LD 50 was assessed as we have previously described. 75 At four doses per experiment, the lowest dose at which a mouse was moribund or dies within 30 days was determined as the approximate LD 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Four independent studies were performed and analysis of the approximate LD 50 was assessed as we have previously described. 75 At four doses per experiment, the lowest dose at which a mouse was moribund or dies within 30 days was determined as the approximate LD 50 .…”
Section: Methodsmentioning
confidence: 99%
“…This paradigm is evident in the interactions between BER that promote HR events (Figure 5). The Engelward laboratory has shown that conditions inhibiting the initiation of BER actually suppress HR in vivo , presumably because the BER intermediates (including SSB or abasic sites) are more recombinogenic than some of the original adducted base substrates of BER [95]. These results show that changes in the balance of activity and protein products in one pathway (BER) can affect processing via another pathway (HR) and may put cells at increased risk of mutation.…”
Section: Interactions Between Dna Repair and Ddr Pathwaysmentioning
confidence: 99%
“…To avoid the accumulation of deleterious damage intermediates, BER must therefore be efficiently and precisely regulated to initiate and complete repair. In fact, the BER intermediates generated by the alkyladenine glycosylase induce more robust HR than the initial alkylation damage in vivo 58 . The impact of BER and DSB repair pathway cross regulation and how the cell cycle phase contributes to pathway crosstalk to maintain genome stability are areas that require further study.…”
Section: Non-homologous End Joining and Homologous Recombination Cmentioning
confidence: 99%